Moderating effect of vocational self-efficacy on the relationship between socioeconomic status, social support, vocational outcome expectation and students’ interest in TVET program, Pakistan - Azeem, Nazia (2021)
The Technical and Vocational Education and Training program (TVET) has been widely acknowledged as one of the most important subjects in the educational system. TVET has been gained attention in numerous national and international contexts. The skilled workforce has a significant role in economic development, industrialization, individual development, and to attract foreign direct investment. Despite the significance of Technical and Vocational Education and Training to rapid economic growth, the program still seems to be far from receiving massive acceptance in Pakistan. Thus, this study examines the moderating effect of vocational self-efficacy on the relationship between socioeconomic status, social support, vocational outcome expectation and students’ interest in the TVET program among secondary school students in Pakistan. For this quantitative research, a questionnaire was used as an instrument for collecting data. Socioeconomic status was measured using instrument developed by Dadje et al. (2015) presented a reduced version of the Aggarwal et al. scale (2005). Meanwhile, social support was measured using Multidimensional Scale of Perceived Social Support (MSPSS) scale developed by Zimet et al. (1988).Vocational outcome expectation was measured using instrument Vocational Outcome Expectations-Revised scale was developed by McWhirter and Metheny (2013) and students’ interest was measured by Interest Scale developed by Ainley (2012) and Baker et al. (2015). It was a descriptive cross-sectional study using a survey method. A total of 386 respondents were selected through multistage proportionate stratified random sampling to participate in this study. The reliability and validity of the research questionnaires were determined using Cronbach alpha and composite reliability. The collected data were analyzed using descriptive statistical tools such as mean and standard deviation; the research hypothesis was formulated and tested using inferential tools. Structural Equation Modeling (SEM) analysis was also employed to test and establish the convergent validity and discriminant validity of the measures. The Pearson Correlation (r) and Structural Equation Modeling were used as the main inferential statistical analysis for this study. The results revealed that all the selected variables such as socioeconomic status, social support, and vocational outcome expectation have a negative and significant correlation with students’ interest in the TVET program. Socioeconomic status was found a strong correlation with students’ interest negatively (r= -0.653, p<.05). Meanwhile, social support was found to have a strong negative correlation with students’ interest (r= -0.700, p<.05). Vocational outcome expectation was also found to have a strong negative correlation with students’ interest (r= -0.757, p<.05) in the TVET program. Based on the PLSSEM analysis, the combination of the three research variables have significantly contributed 71 % (R2 =0.71) to students’ interest in the TVET program. This means that the three independent variables have a strong impact towards the dependent variable. Meanwhile, socioeconomic status (β= - 0.414, p<0.05) was found to be the most dominant factor contributing to students’ interest in the TVET program. Similarly, there was no moderating role of vocational self-efficacy between the relationship of social support and interest in TVET program (β= 0.049, t= 1.034, p >0.05) and vocational outcome expectation and students’ interest in TVET program (β= 0.002, t= 0.851, p >0.05). On the other hand, vocational selfefficacy plays a moderating effect on the relationship between socioeconomic status and students’ interest in the TVET program (β= 0.114, t= 2.738, p < 0.05). Hence, the research model confirms the theory that all these factors are significant in making student interest. Conclusively, all the selected factors showed a significant and negative relationship with students’ interest in the TVET program. This indicates that those who belong to moderately high socioeconomic status, have moderately high social support and moderately high vocational outcome expectation, they are less likely to pursue a TVET program. Thus, these findings of this study provide vital implications for Pakistani educational policymakers in order to encourage interest among school students to pursuit education in the TVET fields expose them to the program as early in the lower secondary level and provide career development program in the TVET fields through counselling service.